Genomic identification of a pair of multidrug-resistant but non-pathogenic Salmonella enterica serovar Goldcoast isolates in southeast China - Yuan, Yongjuan; Li, Ping; Shen, Wei; Li, Min; He, Xiaofei; Zhou, Bin (Frontiers in Microbiology, 2025)
IntroductionSalmonella is an important foodborne pathogen that can induce severe diseases such as gastrointestinal disease and typhoid fever. Accumulating evidence revealed that Salmonella’s resistance to antibiotics also seriously affects human health. Pathogenic Salmonella enterica serovar Goldcoast (S. Goldcoast) was first detected in 2010 in China and was predicted to have an increasing tendency.MethodsThe MacConkey agar, Salmonella Shigella agar, three-sugar iron agar slant, and Gram-stained microscopic examination were used for strain identification. Gram-negative bacteria identification cards explored more properties of the isolates, while antimicrobial susceptibility testing was used to examine the multidrug resistance. The 2nd and 3rd generation sequencing revealed the genetic information of the isolates.ResultsTwo non-pathogenic isolates with multidrug resistance, JS33 and JS34, harbored 42 antibiotic-resistant genes (ARGs) in contig1 and 13 ARGs in contig2, were isolated from a healthy donor living in southeast China and identified as S. Goldcoast (6,8:r:l,w). Interestingly, JS33 and JS34 showed identical responses to more than 20 antimicrobial agents and were resistant to ampicillin, selectrin, chloramphenicol, tetracycline, and streptomycin. However, JS33 differed from JS34 in hydrogen sulfide (H2S) generation. The genomic sequencing identified a deletion in thiosulfate reductase (K08352) in JS34.DiscussionH2S is an essential physiological regulator linked to inflammation and cancer. Therefore, genomic identification of JS33 and JS34 provided us with a better understanding of drug resistance and could be used as model strains to study the effects of microbial H2S production on the host. Since JS33 and JS34 did not induce gastrointestinal infection or other clinical symptoms as previously reported, the appearance of non-pathogenic S. Goldcoast in southeast China warned us to prepare for the prevalence of antimicrobial-resistant S. Goldcoast in China.